Energy management systems : Requirements with guidance for use (ISO 50001:2018(E) - 5087 International Organization for Standardization (Vernier, Geneva : ISO, 2018)
This document specifies requirements for establishing, implementing, maintaining and improving an energy management system (EnMS). The intended outcome is to enable an organization to follow a systematic approach in achieving continual improvement of energy performance and the EnMS. This document: a) is applicable to any organization regardless of its type, size, complexity, geographical location, organizational culture or the products and services it provides; b) is applicable to activities affecting energy performance that are managed and controlled by the organization; c) is applicable irrespective of the quantity, use, or types of energy consumed; d) requires demonstration of continual energy performance improvement, but does not define levels of energy performance improvement to be achieved; e) can be used independently, or be aligned or integrated with other management systems. Annex A provides guidance for the use of this document. Annex B provides a comparison of this edition with the previous edition.